Beyond the batch: Process and material design of polymeric photocatalysts for flow photochemistry - 변지혜; 홍영란; Kai A. I. Zhang (Cell Press, 2021)
The designability of a polymeric photocatalyst is the main factor that facilitates the modification of its physical properties, such as porosity, solubility, and processability, allowing the entry of a polymeric photocatalyst into a flow reactor. Here, we provide a quick overview of recent investigations into how polymeric photocatalysts have been utilized in flow systems through observations in structural engineering and polymerization techniques. We also show representative examples of how the design of a flow setup can lead to improvements in the performance of polymeric photocatalysts. This paper provides insights for choosing the best reactor options for polymeric photocatalysts, depending on the properties and synthetic protocols of the polymers.